Estudio del clima laboral del Gobierno Autónomo Descentralizado Municipal del cantón Rocafuerte - Vélez Bustes, Junior Enrique (2021)
The objective of this project was to evaluate the work environment in the Municipal Decentralized Autonomous Government of the Rocafuerte canton, to improve the management of the Human Talent department. The methodology used was field research, which allowed the extraction of information through interviews and observation, where it was possible to know the current situation of the public servants who work in the different departments of the entity. Then a survey was applied to 94 professionals whose main results indicated that 87% agree with the good working relationship that exists between all their co-workers, 59% disagree with fairness in the treatment and distribution of responsibilities and tasks of the employees, while 53% mentioned they neither agree nor disagree with the lack of training in professional updating. On the other hand, it was concluded that; if there is a good working environment among all, in addition to the fact that it is necessary for the GAD to establish a continuous and effective monitoring to detect in time those shortcomings that usually appear and that cause labor disagreement, it was also possible to know that the technological system they use is deficient delays the activities to be carried out. Likewise, an improvement plan was proposed with the aim of designing strategies that contribute efficiently to the institution, which was socialized and received positively by the competent authorities.